Transient hemiageusia in cerebrovascular lateral pontine lesions. Issue 5 (13th April 2006) - Landis, B N; Leuchter, I; San Millán Ruíz, D; Lacroix, J-S; Landis, T
Abstract : Knowledge of human central taste pathways is largely based on textbook (anatomical dissections) and animal (electrophysiology in vivo) data. It is only recently that further functional insight into human central gustatory pathways has been achieved. Magnetic resonance imaging studies, especially selective imaging of vascular, tumoral, or inflammatory lesions in humans has made this possible. However, some questions remain, particularly regarding the exact crossing site of human gustatory afferences. We present a patient with a pontine stroke after a vertebral artery thrombosis. The patient had infarctions in areas supplied by the anterior inferior cerebellar artery and showed vertical diplopia, right sided deafness, right facial palsy, and transient hemiageusia. A review of the sparse literature of central taste disorders and food preference changes after strokes with a focus on hemiageusia cases is provided. This case offers new evidence suggesting that the central gustatory pathway in humans runs ipsilaterally within the pons and crosses at a higher, probably midbrain level. In patients with central lesions, little attention has been given to taste disorders. They may often go unnoticed by the physician and/or the patient. Central lesions involving taste pathways seem to generate perceptions of quantitative taste disorders (hemiageusia or hypogeusia), in contrast to peripheral gustatory lesions that are hardly recognised as quantitative but sometimes as qualitative (dysgeusia) taste disorders by patients.